Would victims blame victims? Effects of ostracism, sexual objectification, and empathy on victim blaming - Dvir, Maayan; Nagar, Maayan (Frontiers in Psychology, 2022)
In the current research we examined whether ostracism and sexual objectification affects the tendency to blame the victim of sexual harassment. Previous research concerning victim blame examined the attribution of blame considering characteristics of the victim, the perpetrator, and the relation between them. However, no research to date examined whether situational factors of the perceiver can affect their perception and judgement of blame. We propose that sexual objectification and ostracism may elicit empathy toward the victim, and in turn reduce victim blame. In two experimental studies, women were instructed to imagine interacting with a videotaped man who either gazed at their body (objectification), away from them (ostracism), or at their face (treated well). Then, they were asked to read a newspaper article (Study 1) or watch a video (Study 2) portraying encounters in which the man’s sexual advances continued after the woman expressed discomfort and lack of interest. In Study 1, we found that sexually objectified women attributed less blame to the woman compared to women who were treated well, with ostracized women falling in between and marginally different from both. In Study 2, using mediation analysis we found an indirect effect such that sexually objectified women experienced greater empathy toward the victim, which was associated with reduced attribution of blame. It appears that greater similarity between the situation of the perceiver and the situation of the victim elicits greater empathy. This adds to the previous knowledge that personality similarities result in higher empathy.